2015
DOI: 10.1007/978-3-319-19638-1_13
|View full text |Cite
|
Sign up to set email alerts
|

Investors or Givers ? The Case of a Portuguese Crowdfunding Site

Abstract: Abstract. This is the first paper studying the determinants behind the different values raised by project and by investor using data collected from Portuguese crowdfunding platforms. We concluded that higher prize-moneys, expanded ad duration, and stating that the investment will be used for multiple ends tend to maximize the value that investors send to projects. However, there is a downtrend of the raised values observed at the most recent years that generates additional challenges for all interested on buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Overall, the R2 is high for the estimations regarding total raised value per project, but it is low for the estimations regarding percentage of target and raised value per investor. This aligns with the study by Mourão and Costa (2015) and can be interpreted as evidence of the individual motivations behind each one of these investments, which further generate opportunities of research in order to explore other scientific explanations for explaining the values invested by each sponsor. The tests on endogeneity returned significant values, which prove the exogeneity of the instruments.…”
Section: Data Descriptive Statistics and Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Overall, the R2 is high for the estimations regarding total raised value per project, but it is low for the estimations regarding percentage of target and raised value per investor. This aligns with the study by Mourão and Costa (2015) and can be interpreted as evidence of the individual motivations behind each one of these investments, which further generate opportunities of research in order to explore other scientific explanations for explaining the values invested by each sponsor. The tests on endogeneity returned significant values, which prove the exogeneity of the instruments.…”
Section: Data Descriptive Statistics and Resultssupporting
confidence: 73%
“…Three dependent variables were detailed by Mourão and Costa (2015) when they analyzed determinants of crowdfunding projects observed for the Portuguese PPL Crowdfunding: the total value raised by the project, the value raised by the investor, and the target percentage. Independent variables considered in the model were: year, duration of application, number of supporters, type of promoters, population density of the municipality of the promoters, number of applicants, project validity, minimum invested with maximum reward, minimum invested with reward, and the number of targets for the collected money.…”
Section: Determinants Of a Successful Crowdfunding Projectmentioning
confidence: 99%
See 2 more Smart Citations
“…After an empirical study based on projects on Kickstarter, Kuppuswamy and Bayus concluded that when investing, investors are influenced by constellation effect [1]. According to Mourao, the result of a CF project relies largely on the founder's social network and social status [2].…”
Section: Literature Reviewsmentioning
confidence: 99%